Systematics of the Protohermes costalis species-group (Megaloptera: Corydalidae) - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2007)
The dobsonfly genus Protohermes is the largest genus in Megaloptera, with the richest species diversity and the widest geographic distributions. In the present study, the Protohermes costalis species-group is recognised, including 18 species. Eight species are described herein as new: Protohermes acutatus, Protohermes basimaculatus, Protohermes disjunctus, Protohermes lii, Protohermes orientalis, Protohermes stigmosus, Protohermes triangulatus and Protohermes yangi spp. nov. The interspecific phylogeny within the P. costalis species-group is reconstructed by a cladistic analysis. Discussions on the phylogeny and the biogeography of the P. costalis species-group are also made.